New technologies in health promotion - Yahya, B. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1999)
To be effective health promotions professional one needs to posses a number of skills,not the least of which is being an effective communicator. What and how health related information is communicated to the individuals being served are critical factors that directly influence desired outcomes. In today’s age of interactive communications, health promotion professionals must not only be well informed and up-to-date as to content they are delivering but also must be able to utilise the computer, telecommunication and televisual technologies that are readily available.The effective and efficient use of such multimedia system help health promotion professionals not only to disseminate health related information to segmented populations over wide areas (both national and international) but also, and perhaps more importantly, such systems permit interactivity between recipient and provider.